FILSAFAT MORAL IMMANUEL KANT DAN IMPLEMENTASINYA DALAM KEHARMONISAN MASYARAKAT MULTIKULTURAL - Sigit Triyono; Subiyakto, Bambang; Syahruddin, Syahruddin; Zain Fauzi, Muhammad; Jumriani, Jumriani; Helmi Akmal, Muhammad (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2025)
This study examines Immanuel Kant's moral philosophy and its implementation in building a multicultural society. The purpose of this study is to analyze the basic concepts of Kant's moral philosophy, in particular categorical imperatives, and explore their relevance in the context of contemporary multicultural society. The methodology used is a qualitative approach with a literature study method, using primary sources in the form of Kant's original works and secondary sources from various scientific publications in 2015-2024. The data was collected through systematic searches of academic databases such as JSTOR, Google Scholar, and ProQuest, then analyzed using content analysis methods and philosophical hermeneutics. The results show that Kant's moral philosophy, especially universal principles and respect for human dignity, provides a fundamental ethical foundation in building a multicultural society. The implementation of Kantian moral principles can be realized through intercultural dialogue, multicultural education, and inclusive public policy. This research contributes to the development of theoretical and practical discourse in an effort to build a harmonious multicultural society based on Kantian ethics